STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM RANGKA MENINGKATKAN KINERJA KARYAWAN MELALUI ANALISIS SWOT: (STUDY KASUS PADA KOPERASI SYARIAH BENTENG MIKRO INDONESIA) - Akhmad Jauhari, Akhmad Jauhari; Asep Saifudin, Asep Saifudin; Moedigdo Sigit Prakoso , Moedigdo Sigit Prakoso (Cakrawala Akuntansi & Manajemen, 2024)
This research aims to find out how the HR development strategy process is implemented to improve employee performance and what the results of SWOT analysis and HR development strategies are in improving employee performance at Kopsyah BMI. The research design used in this research is descriptive qualitative research and the analytical tool used in analyzing this research is the SWOT Matrix. The results of the analysis show that the process carried out by the company is 1) Holding a training program or training in collaboration with the BMI Institute to be able to improve the competence of employees. 2) Hold job fairs at the best schools around the branch office to find prospective employees who are competent in their fields. 3) Providing recruitment information via social media so that it can be known to many people or prospective employees. 4) Hold training programs related to the use of transaction tools and data input.